Learning to Read and Compose ‘Si Kancil’ Fairy Tale Texts Based on Local Wisdom for Fourth Grade Students of SDN 2 Karangsari Garu - Hema Halimatusyadiah; Disman (International Conference on Elementary Education, 2023)
This study aims to describe learning to read and write the text of the fairy tale 'si kancil' based on local wisdom for fourth grade students at SDN 2 Karangsari Garut, the implementation of learning to write the text of the fairy tale 'si kancil' based on local wisdom of fourth students at SDN 2 Karangsari Garut, evaluation of learning to write the text of the fairy tale 'si kancil' based on local wisdom for fourth grade students at SDN 2 Karangsari Garut. The subjects of this study were fourth grade students and fourth grade teachers at SDN 2 Karangsari Garut. The object of this research is learning to write fairy tale texts based on local wisdom. literacy (fairy tales) is a solution that can be chosen in learning , especially learning Early Reading and Writing (MMP). Literary works have many advantages, including developing character, refining character, language learning tools, and others.Methods are steps taken to facilitate research. Every research is advised to start by determining what will be used in research, this needs to be done because the method is one way that determines the success or failure of a study. This research is a descriptive study that aims at a clear, objective and systematic description of facts existed during the study. The result of this research is that the teacher carries out three stages, starting with planning, implementing, and evaluating learning.